Digital Religion Practices in The Generation Native and Immigrant - Fajrie, Mahfudlah; Muslimin, Khoirul; Arianto, Dwi Agung Nugroho (Jurnal Komunikasi Nusantara, 2024)
This research aims to analyze digital religion practices carried out by digital natives and digital immigrants. The research method used was qualitative with a phenomenological approach, data collection using observation, interviews and virtual documentation via social media accounts and digital platforms. The practice of digital religion is online religious activity. However, in reality digital natives and digital immigrants actually choose to take part in learning or religious studies directly face to face with ustadz or kyai, rather than through online media. The practice of digital religion is only considered as a complement and helps fulfill the need for religious knowledge. In a religious context, social media or digital platforms have not been able to replace the direct religious learning process between ustadz or teachers and their students. This research contributes to media and communication studies, specifically Islamic communication to understand the perceptions of teenagers and parents in responding to digital religion practices which are widespread in various circles of society and other religions. The research is a study of media and religion with a phenomenological perspective with virtual ethnographic supporting data to understand people's religious practices both directly and through digital platforms. Abstrak Penelitian ini bertujuan untuk menganalisis praktik keagamaan digital yang dilakukan oleh digital natives dan digital imigran. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan fenomenologi, pengumpulan data menggunakan observasi, wawancara dan dokumentasi virtual melalui akun media sosial dan platform digital. Praktik agama digital adalah kegiatan keagamaan secara online. Namun pada kenyataannya, para digital native dan digital imigran justru memilih mengikuti pembelajaran atau kajian agama secara langsung dengan bertatap muka dengan ustadz atau kyai, dibandingkan melalui media online. Pengamalan agama digital hanya dianggap sebagai pelengkap dan membantu pemenuhan kebutuhan akan ilmu agama. Dalam konteks keagamaan, media sosial atau platform digital belum mampu menggantikan proses pembelajaran agama secara langsung antara ustadz atau guru dengan santrinya. Penelitian ini memberikan kontribusi pada kajian media dan komunikasi khususnya komunikasi Islam untuk memahami persepsi remaja dan orang tua dalam menyikapi praktik keagamaan digital yang marak di berbagai kalangan masyarakat dan agama lain. Penelitian tersebut merupakan kajian media dan agama berperspektif fenomenologis dengan data pendukung etnografi virtual untuk memahami praktik keagamaan masyarakat baik secara langsung maupun melalui platform digital.